2013
DOI: 10.3390/agronomy3040648
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Bio-Products Sowing the Seeds of Success for Sustainable Agriculture

Abstract: Abstract:Plants have recently been recognized as meta-organisms due to a close symbiotic relationship with their microbiome. Comparable to humans and other eukaryotic hosts, plants also harbor a "second genome" that fulfills important host functions. These advances were driven by both "omics"-technologies guided by next-generation sequencing and microscopic insights. Additionally, these new results influence applied fields such as biocontrol and stress protection in agriculture, and new tools may impact (i) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(79 citation statements)
references
References 42 publications
2
77
0
Order By: Relevance
“…Harnessing the beneficial potential of the plant microbiome to mitigate major crop diseases, such as HLB, is gaining interest as a sustainable approach to improve agricultural production (5,6,32). It has been suggested that the abundances of core members within plant-associated microbial communities, which may stably associate with particular hosts (11,13,15), are a determinant factor in whether the community is functioning in a "healthy" state (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harnessing the beneficial potential of the plant microbiome to mitigate major crop diseases, such as HLB, is gaining interest as a sustainable approach to improve agricultural production (5,6,32). It has been suggested that the abundances of core members within plant-associated microbial communities, which may stably associate with particular hosts (11,13,15), are a determinant factor in whether the community is functioning in a "healthy" state (9).…”
Section: Discussionmentioning
confidence: 99%
“…Under the right circumstances, the microbiome can bolster plant productivity by providing protection against pathogens, among other mechanisms (1)(2)(3)(4). Several studies have indicated that managing microbial taxonomic/functional diversity at the field scale can have positive effects on crop production (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Through their impact on the development of next-generation bio-products, NGS technologies are already an important driver of innovation toward a sustainable agriculture (Berg et al, 2013). The advantages of NGS technologies over classical techniques for microbial community studies are illustrated in Fig.…”
Section: Opportunities For Biocontrol Research In the Microbiome Eramentioning
confidence: 99%
“…Beneficial plant-associated microbes can help plants suppress diseases, stimulate growth, occupy space that would otherwise be taken up by pathogens, promote biotic stress resistance, and increase crop yield and quality by nutrient mobilization and transport (Berg et al 2013). Therefore, the plant microbiome is a key determinant of plant health and productivity.…”
Section: Desert Farming Exploits Plant-microbe Interaction To Improvementioning
confidence: 99%